Editorial de la revista número 4 del año 2019 - Alfie, José (Revista del Hospital Italiano de Buenos Aires, 2019)
Fibromuscular dysplasia is a disease of small- and medium-sized arteries that can cause stenosis, dissections, and aneurysms. It typically affects the renal, carotid, and vertebral arteries, but it can also involve the iliac, femoral, brachial, mesenteric, and coronary arteries. Lucas Aparicio, from the Arterial Hypertension Section of the Department of Internal Medicine, presents the first national registry of fibromuscular dysplasia, initiated five years ago. Neurofibromatosis is a genetic disorder in which tumors form in any part of the nervous system, including the brain, spinal cord, and nerves. María Florencia Correa and Natalia Inés Pasik, from the Department of Internal Medicine, review the epidemiology, molecular aspects, clinical expression, and current management of neurofibromatosis types 1 and 2. Eduardo G. Giacomantone, from the Department of Internal Medicine, reviews the different clinical presentations of depression in general medicine and its treatment. In the Medical Education section, Yasmín Dana Moauro and collaborators from the University Institute of Hospital Italiano evaluated the training of surgical technologists at different universities. PD-1 is a negative regulator of T-cell activity. Its inhibition with monoclonal antibodies activates the antitumor response but may be associated with autoimmune complications. María Paz Micieli Galeazzi and collaborators from the Departments of Dermatology and Allergy and Immunology present the case of a patient treated with pembrolizumab for lung cancer who developed hypothyroidism. Lingual thyroid is an anomaly of thyroid development resulting from failure of the thyroid gland to descend to its prelaryngeal location. Carlos Santiago Ruggeri, Lautaro Acosta, and Ivo Bedini, from the Head and Neck Unit of the Department of Otolaryngology, report the case of a patient with thyroid tissue at the base of the tongue resected via a transoral approach. In the Hospital Italiano in Medline section, two publications are discussed. Santiago Andrés Frid and María Florencia Grande Ratti, from the Department of Health Informatics and the Internal Medicine Research Area, evaluated the implementation of the Virtual Care Program for unscheduled teleconsultations developed in 2018. Agustina Galmarini, from the Department of Ophthalmology, investigated whether antiglaucoma drugs are a factor contributing to lacrimal pathway obstruction.